Localizing mobile nodes in WSNs using neural network algorithm. (2022) - Singh Walia, Gagandeep; Singh, Parulpreet; Singh, Manwinder
Abstract: The most basic and crucial parameter in Wireless Sensor Networks (WSNs) is determining exact location of the node that is meant to be the target. To find the node, the most important parameter is to locate the node's coordinates; otherwise, all of the data gathered by the other sensor nodes would be useless, and communication will be erroneous, perhaps causing interference to all nodes. As a result, the bulk of WSN applications require pinpointing the exact geographical location of the target nodes. Here, for computing the location of randomly moving target nodes an algorithm known as Neural Network algorithm is used. A node whose position is known is normally deployed in the middle of the region which is to be sensed. Acquiring results and comparing performance parameters such as the number of localised nodes, location, and scalability can be used to measure the success of the NNA approach.